Strain sensing with femtosecond inscribed FBGs in perfluorinated polymer optical fibers - Stajanca, Pavol; Lacraz, Amédéé; Kalli, Kyriacos; Schukar, Marcus; Krebber, Katerina (My University, 2016)
In this work, the potential of fiber Bragg gratings (FBGs) in low-loss perfluorinated polymer optical fibers (PF-POFs) is explored. The FBG is femtosecond-inscribed in a commercial multi-mode (MM) PF-POF based on Cytop polymer. Femtosecond inscription leads to creation of a highly saturated grating with a number of higher order reflection peaks visible throughout the visible and near-infrared spectral region. For 2 mm long FBG having a pitch of 2.2895 μm, a total of nine higher-order MM reflection bands are visible spanning from 1548 nm (4th order) to 520 nm (12th order). Strain sensitivity was measured for 6 peak bands in 500-900 nm region, where relatively low cost CCD based spectrometers and broadband LEDs are available. Strain sensitivity increases almost linearly with increasing initial peak wavelength, growing from 4.82 ± 0.02 nm/% measured for 12th order peak at 517 nm to 8.12 ± 0.04 nm/% measured for 7th order peak at 883 nm. These values correspond to roughly 20 % higher sensitivity than silica FBGs exhibit in this spectral range. The gratings in PF-POFs combine the higher strain sensitivity and low-loss operation while maintaining the mechanical advantages of polymer optical fibers. Therefore, they hold a high potential for considerable broadening of polymer optical fiber Bragg gratings application range.
Keywords: Cytop; Fiber Bragg gratings; Fiber optics sensors; Perfluorinated polymer optical fiber; Strain sensitivity